Neobruchidius lovie, new genus and new species from Latin America (Coleoptera: Chrysomelidae: Bruchinae) - Johnson, C. D.; Romero-Napoles, J. (Zootaxa, 2006)
The new genus Neobruchidius is described principally because of the single spine near the apex of the hind femur of all ten species. This and other characters differentiate it from other genera in the New World and ally it to the Old World genus Bruchidius, hence the name. Seven of the ten species of Neobruchidius were all originally described in the genus Acanthoscelides by Johnson and one is the new species Neobruchidius lovie. The nine species are Neobruchidius barinas, N. canar, N. curimagua, N. guatemala, N. lituratus, (Sharp), N. macheta, N. tabidus (Erichson), N. tibiospinalis, and N. zacatlan. A discussion of the genus is provided as is a key to species, and some comments on allometry in adult bruchids due to seed size of their hosts. Neobruchidius lovie differs from species in the genus Sennius principally by lacking hinge sclerites in the median lobe of the male genitalia and with a mucro on the apex of the hind tibia that is much shorter than 0.25 times as long as the first hind tarsomere. Most species of Sennius lack a mucro or almost so.